Genomic simulation for the study of data transformation efficiency in the genetic evaluation of cattle in the presence of heterogeneity - 10.4025/actascianimsci.v34i1.10664 - Antonio Policarpo Souza Carneiro; Paulo Luiz Souza Carneiro; Ricardo Frederico Euclydes; Sebastião Martins Filho; Fabyano Fonseca Silva; Paulo Roberto Cecon (Acta Scientiarum. Animal Sciences, 2011)
Efficiency of data transformation strategies is evaluated to correct heterogeneity among cattle in the genetic evaluation of bulls, cows and progenies. Four data structures of bovine weaning weights were simulated: herds with and without heterogeneity for means and variances, and herds with and without genetic connectedness. In the genetic evaluations, data were used in the original scale and transformed (Logarithmic, Square root, standardization and ratio by phenotypic standard deviation). The evaluated data transformation strategies were not efficient in eliminating the negative effects of heterogeneity among cattle in the genetic evaluation of bulls, cows and progenies.